Outcome evaluation for the CCAFS project LED Dairy China 2019-2021 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Outcome and expected income evaluation amongst the target groupsthat are expected to benefit from the research project WP1 LED Dairy China: dairy processingcompanies, policy makers authorities, dairy farmers, mitigation experts of the involved researchinstitutes and experts and consultants.